Human Trafficking pada Masa Pandemi COVID-19 di Perbatasan Darat Malaysia-Indonesia, Kalimantan Barat - Rupita Rupita; Herlan Herlan; Zakiah Hassan Gaffar; Syarifah Ema Rahmaniah; Nikodemus Niko (Jurnal Masyarakat Maritim, 2021)
The covid-19 pandemic threatens public health alone, therefore most governments in various countries in the world affected by covid-19 take steps in the form of mobility restriction policies to prevent the spread of the virus in the community this also applies in Indonesia. Restrictions on people's mobility make the problems experienced by the community more complex and difficult to control, the number of mass layoffs becomes a trigger for high unemployment in Indonesia. This research uses descriptive qualitative methods. Data collection is done through an online repository, by filtering keywords in search; criminal acts of trafficking, women migrant workers, protection of migrant workers and handling of trafficking cases in the period of emigrants. Each author is tasked with collecting data based on search keywords. Based on the results of research, the high unemployment rate in the pandemic period became one of the main triggers for the criminal act of trafficking in persons. The situation of female migrant workers working abroad is increasingly complex because some of them are undocumented and some have been over-stayers. There are currently around 6 to 8 million Indonesian migrant workers abroad and the majority of them are women. Cases of human trafficking in the border region during the COVID-19 pandemic increased with economic mode. The closure of cross-border postal access is not effective enough in suppressing cases of trafficking at the country's borders. Various efforts have been made by the Indonesian government ranging from implementing policies to efforts to cooperate with various stakeholders — namely the government as regulators, policy makers, as well as law enforcement, and private parties as business actors / recruiters of labor and banking, as well as civil society institutions that are the driving force – to seek protection for Indonesian migrant workers abroad.